Tailored multilevel approaches in vibrational structure theory: A route to quantum mechanical vibrational spectra for complex systems. Issue 3 (29th June 2020) - König, Carolin
Abstract: Vibrational spectroscopies have emerged as important tools to elucidate structures and processes in life sciences. The interpretation of vibrational spectra requires, in most cases, computational assistance and account for anharmonic effects. Pushing the size limitations of anharmonic vibrational structure calculations is therefore of great interest. Fortunately, interpretation of the experimental results often requires only a limited part of the vibrational spectrum. Hence, it can be expected that multilevel approaches, focusing computational effort on the relevant parts, are highly beneficial. Still, such approaches are rather sparse in the field of vibrational structure theory. In this perspective, we outline the present status on multilevel static vibrational wave functions and rectilinear vibrational coordinates. We further foresee how those ingredients can be combined to formulate a comprehensive multilevel vibrational structure framework. Abstract : Vibrational spectroscopies are crucial tools to elucidate structures and processes in biomolecular systems. Their interpretation requires accurate but feasible computational methods. Fortunately, it is often sufficient to focus the computational effort on the relevant parts of the spectrum. Hence, tailored multilevel approaches in vibrational structure theory are emerging. This perspective discusses the current state of these methods and how existing methodologies may be combined and extended to meet the requirements posed by complex biomolecular systems.